Treatment of chronic itch in systemic disease : Current standards - Mettang, T.; Staender, S.; Kremer, Andreas (Internist, 2015)
Chronic itch (CI) is a frequent and sometimes tormenting symptom in many skin and systemic diseases. In systemic diseases, it mostly appears on primarily unaffected skin. As a sequelae of intense scratching, secondary skin lesions such as excoriations, scars, and prurigo nodularis may occur. Due to the lack of valid pathogenetic concepts and good clinical trials, the therapy of CI remains mostly symptomatic. In Europe almost all drugs used to treat CI are not approved for this indication. CI is frequent in patients with chronic kidney diseases in advanced stages. Gabapentin and pregabalin, anticonvulsants, and centrally acting calcium channel blockers have been shown to exert a profound effect in CI. Furthermore, UVB phototherapy has been proven to attenuate pruritus in uremic patients. Randomized controlled studies have recently shown that nalfurafine, a ?-opioid receptor agonist, is able to ameliorate itch in patients with uremic itch. In patients suffering from cholestatic itch, the anion exchange resin colestyramine and rifampicin are effective antipruritic drugs. Furthermore, µ-opioid receptor antagonists and sertraline may be used to alleviate CI in hepatic diseases. In refractory cases, naso-biliary drainage or albumin dialysis are effective invasive procedures. For the treatment of chronic itch in hematological diseases no controlled trials have been performed so far. The mainstay in these cases is to treat the underlying disease.
EVALuna2:1848